P192Opposing effects of cAMP/PKA and cAMP/Epac signalling on in vitro angiogenesis: role of Rho gtpases. (15th July 2014) - Aslam, M; Nef, H; Troidl, C; Hamm, C; Guenduez, D
Abstract: Background: cAMP signalling regulates several endothelial functions such as endothelial barrier integrity, vascular tone, and both physiological and pathological angiogenesis. cAMP mediates these effects via activation of its two well characterised effectors i.e. PKA and Epac (exchange protein directly activated by cAMP). We have previously shown that activation of both cAMP-effectors stabilises endothelial barrier via activation of different signalling pathways. The aim of the present study was to analyse the effects of these cAMP effectors on angiogenesis in vitro. Methods: The study was carried out on cultured human umbilical vein endothelial cells (HUVEC). cAMP analogues, 8-CPT-cAMP (200 μM), 6-Bnz-cAMP (50 μM) and Forskolin (FSK; 5 μM) were used to activate Epac, PKA or adenylyl cyclase, respectively. In vitro angiogenesis was analysed by wound healing, tube formation and spheroid sprouting assays. Results: Specific activation of either PKA or Epac induced HUVEC proliferation and and collective migration (wound healing) which was accompanied by enhanced phosphorylation of Akt (at Ser473) and p42/44 MAPK. Both PKA and Epac-induced HUVEC proliferation and migration was abrogated by inhibitors of both Akt and p42/44 MAPK. Accordingly, specific activation of PKA induced endothelial cell tube formation and promoted sprouting of spheroid in 3-D collagen gels. Surprisingly, specific activation of Epac abrogated endothelial cell tube formation and VEGF-induced sprouting. When both PKA and Epac were activated simultaneously (with FSK), the effect of PKA surpased the inhibitory effect of Epac. Accordingly, the inhibition of Epac resulted in enhanced effect of PKA activation. Although activtion of both PKA and Epac induced Rac1 activation, however, both have differential effects on RhoA activity. PKA antagonised RhoA activity, while Epac caused an activation of RhoA. Inhibition of either RhoA activity or downstream Rho kinase (ROCK) alone resulted in increased HUVEC tube formation and sprouting and abrogated completely the anti-angiogenic effect of Epac activation. Similarly, specific activation of RhoA abrogated PKA-induced angiogenesis. Conclusion: The data of present study demonstrate that cAMP/PKA and cAMP/Epac signalling pathways have differential effects on in vitro angiogenesis. PKA activation promotes while Epac activation antagonises angiogenesis. This differential effect is due to opposite effects of both signalling pathways on RhoA/ROCK signalling.